Compatibility of the Incompatible: How Does Asymmetric Power Lead to Coexistence of Trust and Distrust in Adversarial Policy Networks? - Lee, Jeongyoon; Lee, Junesoo (International Journal of Public Administration, 2024)
Asymmetric power has been found to hinder the development of trust that is essential for structuring policy subsystems or networks. Using a multinomial logistic analysis of a local hydraulic fracturing policy network in New York, our findings indicate that (1) power imbalance affects the coexistence of trust and distrust and (2) power imbalance interacting with certain types of social relationships (policy communication, regulation, and knowledge exchange) leads to the coexistence of trust and distrust. We suggest three implications for the governance of policy networks and policy process literature: increasing levels of trust do not guarantee decreasing levels of distrust, asymmetric power has an impact on structuring “ambivalent” relations, and adversarial policy subsystems can take four structural forms depending on the levels of trust and distrust.